Penerapan Woolwich Massage terhadap Produksi ASI dan Pencegahan Bendungan ASI pada Postpartum Sectio Caesarea - Ni Komang Ayu Gita Suari; Merida Simanjuntak (Buletin Kesehatan: Publikasi Ilmiah Bidang kesehatan, 2024)
Breast milk contains nutrients needed by babies aged 0-6 months in the process of growth and development. The application of woolwich massage therapy aims to increase breast milk production and prevent the occurrence of breast milk dams in postpartum mothers. The study was conducted on postpartum mothers with milk production problems. The descriptive research method with a case study approach accompanied by the application of evidence-based nursing practice. The application is carried out by massaging an area of 1-1.5 cm above the mammal areola, precisely the lactive sinuses. The action is carried out 2 times a day with an intervention duration of 15 minutes for 2 days. The results showed that woolwich massage therapy in postpartum sectio caesarea mothers has not been shown to significantly increase breast milk production, because colostrum production is still limited to 1 to 4 days after delivery. However, it is proven to be able to reduce breast swelling and provide a sense of comfort and relaxation to the mother. Woolwich massage therapy is effectively applied to facilitate breast milk production and can reduce breast swelling so that the mother feels comfortable and relaxed.